Epithelial‐mesenchymal transition via transforming growth factor beta in pancreatic cancer is potentiated by the inflammatory glycoprotein leucine‐rich alpha‐2 glycoprotein. Issue 3 (4th February 2019) - Otsuru, Toru; Kobayashi, Shogo; Wada, Hiroshi; Takahashi, Tsuyoshi; Gotoh, Kunihito; Iwagami, Yoshifumi; Yamada, Daisaku; Noda, Takehiro; Asaoka, Tadafumi; Serada, Satoshi; Fujimoto, Minoru; Eguchi, Hidetoshi; et al.
Abstract : We previously showed that an inflammation‐related, molecule leucine‐rich alpha‐2 glycoprotein (LRG) enhances the transforming growth factor (TGF)‐β1‐induced phosphorylation of Smad proteins and is elevated in patients with pancreatic ductal adenocarcinoma (PDAC). As TGF‐β/Smad signaling is considered to play a key role in epithelial‐mesenchymal transition (EMT), we attempted to clarify the mechanism underlying LRG‐related EMT in relation to metastasis in PDAC. We cultured LRG‐overexpressing PDAC cells (Panc1/LRG) and evaluated the morphology, EMT‐related molecules and TGF‐β/Smad signaling pathway in these cells. We also assessed the LRG levels in plasma and resected specimens from patients with PDAC. Inflammatory cytokines induced LRG production in PDAC cells. A spindle‐like shape was visualized more frequently than other shapes in Panc1/LRG with TGF‐β1 exposure. The expression of E‐cadherin in Panc1/LRG was decreased with TGF‐β1 exposure. Invasion increased with TGF‐β1 stimulation of Panc1/LRG. The phosphorylation of smad2 in Panc1/LRG was increased in comparison with parental Panc1 under TGF‐β1 stimulation. In the plasma LRG‐high group, the recurrence rate tended to be higher and the recurrence‐free survival (RFS) tended to be worse in comparison with the plasma LRG‐low group. LRG enhanced EMT induced by TGF‐β signaling, thus indicating that LRG has a significant effect on the metastasis of PDAC. Abstract : Leucine‐rich alpha‐2 glycoprotein enforced transforming growth factor‐inducing epithelial‐mesenchymal transition.